Solutions journalism news at the intersection of hope, leadership, and expertise - Dodd, Bill (College teacher) (Lexington Books, 2021)
"As audiences increasingly avoid negative news, journalists are being called upon to tell optimistic stories about the future. This book explores emerging solutions reporting practices while arguing for a journalism based on hope psychology and a pluralist conception of leadership and expertise"--